Nguyen Viet Hung on food-borne diseases and public health shocks in East Asia and the Pacific - Hung Nguyen-Viet (International Food Policy Research Institute, 2014)
Parallel Sessions 9: Improving Resilience to Shocks in Regional Contexts. Nguyen Viet Hung, Scientist, Food Safety and Zoonoses program, International Livestock Research Institute (ILRI) in Vietnam and Center for Public Health and Ecosystem Research (CENPHER), Hanoi School of Public Health, Vietnam, panelist at Parallel Session 9E on "Building Resilience to Food-borne Diseases and Public Health Shocks in East Asia and the Pacific." IFPRI 2020 conference on Building Resilience for Food and Nutrition Security, May 15-17, 2014, Addis Ababa, Ethiopia. More information at http://www.2020resilience.ifpri.info